1992
DOI: 10.1093/jpepsy/17.6.725
|View full text |Cite
|
Sign up to set email alerts
|

Children with Physical Handicaps and Their Mothers: The Interrelation of Social Support, Maternal Adjustment, and Child Adjustment

Abstract: Examined the interrelation of maternal adjustment, mother-child interaction, and child adjustment in 29 families of children with spina bifida and without mental retardation and in 28 families of children without handicaps. A multivariate, ecological model proposed that adjustment of mother and child depends on the adaptiveness of maternal response to the stress of the physical handicap and on the ability of mothers to create an optimal caregiving environment through mother-child interaction. Analyses examinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0
7

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 0 publications
4
62
0
7
Order By: Relevance
“…Previous research has shown that social support, family functioning, and stress management may constrain resources with regard to caregiver health outcomes. 7,12,29,[35][36][37][38][39][40][41] The proposed direct link between social support and health was not replicated in this study. Clearly, the influence of social support provided by extended family, friends, and neighbors on health outcomes was secondary to that of the immediate family working closely together.…”
Section: Discussionmentioning
confidence: 71%
“…Previous research has shown that social support, family functioning, and stress management may constrain resources with regard to caregiver health outcomes. 7,12,29,[35][36][37][38][39][40][41] The proposed direct link between social support and health was not replicated in this study. Clearly, the influence of social support provided by extended family, friends, and neighbors on health outcomes was secondary to that of the immediate family working closely together.…”
Section: Discussionmentioning
confidence: 71%
“…Some document the presence of increased family distress [8,20,26,27], reduced marital satisfaction [24,28] and inadequate levels of social support [24,29,30], while others suggest that the functioning of these families is not more problematic [16,18,31], and that marital satisfaction and social support are no different from that of couples who have children without disabilities [16,18,20,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted with families of children with brain injury provides evidence of an effect of child status on parents, and parental status upon the injured child, [17][18][19][20] to be expected given the relationship of parents and young children. There is less evidence for a reciprocal relationship between functioning of adults who have sustained a moderate to severe TBI and family functioning.…”
mentioning
confidence: 99%